2021
DOI: 10.1021/acsami.1c04829
|View full text |Cite
|
Sign up to set email alerts
|

Designing of Highly Efficient Oxygen Evolution Reaction Electrocatalysts Utilizing A Correlation Factor: Theory and Experiment

Abstract: The theoretical prediction of the catalytic activity is very beneficial for the design of highly efficient catalysts. At present, most theoretical descriptors focus on estimating the catalytic activity and understanding the enhancement mechanism of catalysts, while it is also quite important to find a factor to correlate the descriptors with preparation methods. In this work, a correlation factor, the d electron density of transition metal ions, was developed to correlate the d band center values of transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…On the one hand, the approximate linear relationships between ε d and D d values indicated that, as shown in Figure 5 B, the local electronic structures of active site (ε d ) could be quantitatively adjusted by its coordination atomic plus electronic structures of D d . 13 , 48 On the other hand, the D d values were increased from HEO- O -1 to HEO-3 systems on account of the shortened Fe-O bond, which were consistent with the experimental XPS measurements. Hence, the pre-designed correlator D d could effectively correlate the modification method and chemical activity.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…On the one hand, the approximate linear relationships between ε d and D d values indicated that, as shown in Figure 5 B, the local electronic structures of active site (ε d ) could be quantitatively adjusted by its coordination atomic plus electronic structures of D d . 13 , 48 On the other hand, the D d values were increased from HEO- O -1 to HEO-3 systems on account of the shortened Fe-O bond, which were consistent with the experimental XPS measurements. Hence, the pre-designed correlator D d could effectively correlate the modification method and chemical activity.…”
Section: Resultssupporting
confidence: 88%
“…The pre-designed formula of D d and the occupied volume of d electrons ( V d ) was following 48 : where r Fe and r O denoted the ionic radius of Fe 3+ and O 2- ions. CN = 5 denoted the coordination number of surface Fe 3+ ions.…”
Section: Methodsmentioning
confidence: 99%